2011
DOI: 10.1128/iai.01105-10
|View full text |Cite
|
Sign up to set email alerts
|

Infectivity Acts asIn VivoSelection for Maintenance of the Chlamydial Cryptic Plasmid

Abstract: Chlamydia trachomatis contains a conserved ϳ7.5-kb plasmid. Loss of the plasmid results in reduced glycogen accumulation, failure to activate TLR2, and reduced infectivity. We hypothesized that reduced infectivity functions as a means of selection for plasmid maintenance. We directly examined the biological significance of the reduced infectivity associated with plasmid deficiency by determining the relative fitness of plasmid-deficient CM972 versus that of wild-type C. muridarum Nigg in mixed inocula in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
53
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 35 publications
0
53
2
Order By: Relevance
“…glycogen accumulation) and in controlling the expression of certain genes on the Chlamydia chromosome. Overall, studies of infection with both wild‐type and plasmid‐free C. trachomatis and C. muridarum strains in mouse urogenital infection indicate that the plasmid modulates infectivity and may be essential for pathogenic immune responses (O'Connell et al ., 2007; Carlson et al ., 2008; Olivares‐Zavaleta et al ., 2010; Russell et al ., 2011). It is all but certain that either C. muridarum plasmid gene products or products of plasmid responsive loci on the bacterial chromosome engage Toll‐like receptor‐2 (TLR‐2) causing deleterious responses in mouse urogenital infections with C. muridarum (O'Connell et al ., 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…glycogen accumulation) and in controlling the expression of certain genes on the Chlamydia chromosome. Overall, studies of infection with both wild‐type and plasmid‐free C. trachomatis and C. muridarum strains in mouse urogenital infection indicate that the plasmid modulates infectivity and may be essential for pathogenic immune responses (O'Connell et al ., 2007; Carlson et al ., 2008; Olivares‐Zavaleta et al ., 2010; Russell et al ., 2011). It is all but certain that either C. muridarum plasmid gene products or products of plasmid responsive loci on the bacterial chromosome engage Toll‐like receptor‐2 (TLR‐2) causing deleterious responses in mouse urogenital infections with C. muridarum (O'Connell et al ., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It is not possible to predict whether any of these SNPs contributed directly to the differences we have observed in the mouse model. However, our observations are quite consistent with the aforementioned in vivo observations of plasmid‐free strains in human disease (Bjartling et al ., 2009; Harris et al ., 2012) and in other animal models (O'Connell et al ., 2007; Carlson et al ., 2008; Olivares‐Zavaleta et al ., 2010; Russell et al ., 2011). Thus, we feel the most logical inference is to attribute the differences seen to presence and function of the plasmid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may reflect procedural differences in the in vitro assays performed, e.g., determination of plaquing efficiency versus plating efficiency (6). Most recently, we observed that coculture competition assays in vitro are more reflective of in vivo differences than differences in plaquing efficiency (35) and could facilitate further analysis of 25667R's infectivity. An additional confounding factor is the differences in cell attachment/entry associated with strains of the C. trachomatis LGV serogroup, including L2/434/Bu and 25667R (11), that might mask or override plasmid-associated infectivity differences.…”
mentioning
confidence: 84%
“…Although we were unable to investigate the contribution of glycogen to infectivity in CTD153 because we did not recover spontaneous "revertants" of the infectivity defect, we were also unable to demonstrate a role for glycogen in infectivity in C. muridarum, because plasmid-deficient CM3.1, which displays wild-type infectivity in vitro, had a normal course of infection when inoculated intravaginally into mice and established infection in the oviducts at levels that were not significantly different from the parental Nigg strain (29) despite its inability to accumulate glycogen. Recently, genetic characterization of both C. muridarum strains CM972 and CM3.1 via comparative genome hybridization revealed no additional mutations other than loss of the plasmid to account for the phenotypic changes in CM972, and a single base substitution in TC0236 was detected in CM3.1 that may be responsible for restored infectivity (35).…”
mentioning
confidence: 99%